A comparative study of transcervical foley’s catheter with intracervical PGE2 gel for pre-induction cervical ripening - ., Anupma; Karya, U.; Gaikwad, Harsha S.; ., Anamika; ., Shalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To compare the efficacy of transcervical foley’s catheter with intracervical PGE2 gel for pre -induction cervical ripening. Methods: It was a prospective interventional study conducted between April 2012 to April 2013 in the department of obstetrics and gynecology at L. L. R. M. medical college and S. V. B. P. hospital Meerut. A total of 80 pregnant women of ≥28 weeks of gestation with bishop score less than or equal to 4 and with various indications for induction of labour were randomly allocated to receive intracervical PGE2 gel (Group A) or transcervical foley’s catheter (Group B). Bishop score was repeated after 6 hours by the same person and the results were compared. Results: The groups were comparable with respect to maternal age, gestational age, indications of induction of labour and initial bishop’s score. The intragroup results were calculated by Wilcoxon signed rank test and intergroup results were calculated by Mann Whitney U-test. The change in bishop score in PGE2 group was 3 and in foley’s group was 3.25 after 6 hours of induction (interquartile range of median) which is significant. The mean change in bishops score was 2.65 in PGE2 group and 3.1 in foley’s group after 6 hours of induction and was significant, however the bishop’s score was comparable in both the groups and statistically insignificant. Conclusions: Both foley’s catheter and PGE2 gel are equally effective in pre-induction cervical ripening of cervix.